EVALUASI UPRATING IPAM WIROLEGI PDAM JEMBER DITINJAU DARI ASPEK TEKNIS - Ady Setiawan; Wahyono Hadi (Program Studi Teknik Lingkungan, Universitas Pembangunan Nasional Veteran Jawa Timur, 2020)
Wirolegi IPAM surpassed the decline in quantity and quality in recent years. This decrease is due to the existing condition of clean water production produced by Wirolegi IPAM that still has not met the agreed target, while the production capacity is 22 L / s which serves around 2,000 house connections. From the existing condition, Wirolegi IPAM currently produces output with a capacity that is not yet maximum, from 2x10 lpd it is only able to produce less than 15 lpd. This study aims to evaluate the condition of IPAM so that it can be done to improve Wirolegi IPAM to get the advantages and optimal production quality according to PP No. 82 of 2001. The method used is there; ah quantitative descriptive method. From the evaluation, it was found that there were obstacles in the coagulation-flocculation unit which resulted in turbulence in the sedimentation tank so the filter was unable to work optimally and the condition of the IPAM that needed to be improved. It is necessary to uprating and optimizing from 2x10 lpd to 2x20 lpd by healing the inside and adding dimensions to the coagulation-flocculation, sedimentation and filtration units